Photoluminescence Properties of Layered Pb1-xCdxI2 Solid Solutions - Gnatenko, Yu.P.; Fur’yer, M.S.; Bukivskij, P.M.; Skubenko, P.A.; Piryatinski, Yu.P.; Gamernyk, R.V. (Ukrainian Journal of Physics, 2022)
We have studied the photoluminescence spectra, including the time-resolved ones, and the photodiffusion spectra of PbI2 crystals and Pb1-xCdxI2 solid solutions. It is established that these crystals have monopolar (hole) photoconductivity. The possibility of the formation of PbI2 clusters with various sizes in solid solutions is shown. It is found that the value of splitting between Γ3–- and Γ1–-exciton states in such clusters is 30 and 36 meV for x = 0.50 and x = 0.70, respectively. We have revealed that, for x = 0.50, the self-trapping excitons in PbI2 clusters happens.